2019
DOI: 10.1186/s13075-019-1829-7
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of microRNA expression in monocytes and CD4+ T lymphocytes from patients with axial spondyloarthritis

Abstract: BackgroundMicroRNAs (MiRs) play an important role in the pathogenesis of chronic inflammatory diseases. This study is the first to investigate miR expression profiles in purified CD4+ T lymphocytes and CD14+ monocytes from patients with axial spondyloarthritis (axSpA) using a high-throughput qPCR approach.MethodsA total of 81 axSpA patients fulfilling the 2009 ASAS classification criteria, and 55 controls were recruited from October 2014 to July 2017. CD14+ monocytes and CD4+ T lymphocytes were isolated from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 76 publications
1
17
0
Order By: Relevance
“…Recently, differential expression of miR-2137 was observed in bone marrow-derived macrophages after infection with Porphyromonas Gingivalis bacteria (23), and inhibiting miR-2137 increased expression of the anti-inflammatory cytokine IL-10 suggesting that miR-2137 may be pro-inflammatory following O3 exposure. We also observed an O3-induced upregulation of EV miR-126-3p, a well-studied pro-inflammatory miRNA (15). miR-126-3p is also upregulated in inflammatory bowel disease (IBD), in which it targets nuclear factor-kappaB inhibitor alpha (IκB) (14,54) and impairs intestinal epithelial barrier function (7).…”
Section: Discussionmentioning
confidence: 80%
“…Recently, differential expression of miR-2137 was observed in bone marrow-derived macrophages after infection with Porphyromonas Gingivalis bacteria (23), and inhibiting miR-2137 increased expression of the anti-inflammatory cytokine IL-10 suggesting that miR-2137 may be pro-inflammatory following O3 exposure. We also observed an O3-induced upregulation of EV miR-126-3p, a well-studied pro-inflammatory miRNA (15). miR-126-3p is also upregulated in inflammatory bowel disease (IBD), in which it targets nuclear factor-kappaB inhibitor alpha (IκB) (14,54) and impairs intestinal epithelial barrier function (7).…”
Section: Discussionmentioning
confidence: 80%
“…Deregulation of hsa-miR-28-5p is related to rheumatic diseases, such as axial spondyloarthritis and rheumatoid arthritis. 49,50 Herein, we first found that hsa-miR-28-5p was up-regulated in osteonecrosis of the femoral head. In addition, the down-regulated RELA proto-oncogene, NF-kB subunit (RELA, also called p65) was one of the targets of hsa-miR-28-5p.…”
Section: Discussionmentioning
confidence: 96%
“…In AS, immunopathogenesis and bone remodeling are the mainstays involved in disease pathogenesis. Accordingly, miRNAs might be implicated in AS diagnostic, prognostic, and therapeutic processes [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the important role of circulating miRNAs in AS pathogenesis has been explored [8]. T cells and peripheral blood mononuclear cells (PBMCs) of AS patients have shown an altered miRNA expression which is involved in specific pathways in the disease pathogenesis [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation